Modular Organization and Combinatorial Energetics of Proline–Tyrosine Nuclear Localization Signals - Süel, Katherine E (Public Library of Science, 2008)
Proline–tyrosine nuclear localization signals (PY-NLSs) are recognized and transported into the nucleus by human Karyopherin (Kap) β2/Transportin and yeast Kap104p. Multipartite PY-NLSs are highly diverse in sequence and structure, share a common C-terminal R/H/KX(2–5)PY motif, and can be subdivided into hydrophobic and basic subclasses based on loose N-terminal sequence motifs. PY-NLS variability is consistent with weak consensus motifs, but such diversity potentially renders comprehensive genome-scale searches intractable. Here, we use yeast Kap104p as a model system to understand the energetic organization of this NLS. First, we show that Kap104p substrates contain PY-NLSs, demonstrating their generality across eukaryotes. Previously reported Kapβ2–NLS structures explain Kap104p specificity for the basic PY-NLS. More importantly, thermodynamic analyses revealed physical properties that govern PY-NLS binding affinity: (1) PY-NLSs contain three energetically significant linear epitopes, (2) each epitope accommodates substantial sequence diversity, within defined limits, (3) the epitopes are energetically quasi-independent, and (4) a given linear epitope can contribute differently to total binding energy in different PY-NLSs, amplifying signal diversity through combinatorial mixing of energetically weak and strong motifs. The modular organization of the PY-NLS coupled with its combinatorial energetics lays a path to decode this diverse and evolvable signal for future comprehensive genome-scale identification of nuclear import substrates.